Gaya Bahasa Perbandingan dalam Retorika Ceramah Ustadz Abdul Somad di Youtube : Episode "Ngakak Parah! Ceramah Terbaru Ustadz Abdul Somad 2026" (Kajian Retorika) - Irma I; Rhani Febria (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the types of comparative figurative language and their functions in constructing the rhetorical strategies of ethos, pathos, and logos in a sermon delivered by Abdul Somad, featured in the YouTube video entitled "Ngakak Parah! Ceramah Terbaru Ustadz Abdul Somad 2026 Bikin Jamaah Gak Kuat Tahan Tawa." This research employs a qualitative approach with a descriptive method. Data were collected through documentation, observation, and note-taking techniques from utterances in the 40-minute and 54-second video, and were analyzed through data reduction, classification, and interpretation stages. Data validity was ensured through technique triangulation. The findings reveal nine types of comparative figurative language used in the sermon: metaphor, personification, antithesis, hyperbole, allegory, periphrasis, pleonasm, anticipation, and correction (correctio). Functionally, these figurative expressions work synergistically to construct rhetorical strategies: ethos is built through consistency between the values taught and the preacher’s behavior; pathos is developed through humor, emotional surprises, and situations that resonate with the audience’s everyday experiences; and logos is established through rational cause-and-effect arguments concerning modern social phenomena.